Agricultural policy in disarray: Reforming the Farm Bill - Vos, Rob (2018)
Rob Vos BOOK LAUNCH Agricultural Policy in Disarray: Reforming the Farm Bill Co-Hosted by IFPRI and American Enterprise Institute DEC 12, 2018 - 12:15 PM TO 01:45 PM EST